The decision of the Court of First Instance of Tangier (Morocco) of January 30, 2017 about extramarital filiation: affirmation of tradition or a step towards innovation? - El Ouazzani Chahdi, Salma (CUADERNOS DE DERECHO TRANSNACIONAL, 2019)
In Moroccan law, DNA test is limited to the recognition of paternity within the matrimonial relationship, so that extramarital filiation cannot produce any of the legal effects between father and son. The Court of First Instance of Tangier (Morocco) has broken with a deep-rooted jurisprudential tradition by recognizing the paternity of the child through biological test. Such decision was rejected in the second degree. This is incompatible with the Moroccan social reality; it also violates the fundamental principles of the Constitution and the provisions of international conventions ratified by Morocco.